2002
DOI: 10.1136/heart.88.5.488
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and recurrent cardiac events after coronary artery bypass graft: long term outcomes in a population study

Abstract: Objective: To determine 30 day mortality, long term survival, and recurrent cardiac events after coronary artery bypass graft (CABG) in a population. Design: Follow up study of patients prospectively entered on to a cardiothoracic surgical database. Record linkages were used to obtain data on readmissions and deaths. Patients: 8910 patients undergoing isolated first CABG between 1980 and 1993 in Western Australia. Main outcome measures: 30 day and long term survival, readmission for cardiac event (acute myocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 39 publications
1
37
1
1
Order By: Relevance
“…A recent analysis by Domburg et al [11] from the Netherlands showed a 10-year mortality of 23% in a series of 1041 consecutive patients who underwent CABG in the 1970s and in the 1980s. In a population-based study from Western Australia, Bradshaw et al [22] found a 10-year mortality of 27% for men and 30% for women who had CABG between 1980 and 1993. A slightly higher mortality than in our study is explained by the inclusion of older age groups.…”
Section: Discussionmentioning
confidence: 97%
“…A recent analysis by Domburg et al [11] from the Netherlands showed a 10-year mortality of 23% in a series of 1041 consecutive patients who underwent CABG in the 1970s and in the 1980s. In a population-based study from Western Australia, Bradshaw et al [22] found a 10-year mortality of 27% for men and 30% for women who had CABG between 1980 and 1993. A slightly higher mortality than in our study is explained by the inclusion of older age groups.…”
Section: Discussionmentioning
confidence: 97%
“…However, experiences indicate that a substantial part of the patients have recurrence of symptoms over time [4,5,21]. Therefore, in Table 2 Independent predictors of an inferior QoL 10 years after CABG-All survivors included NHP total score > 7.8 ( = median) p OR (95% ci) a PGWB total score < 105 ( = median) p OR (95% ci) a long-term perspective, many patients still have an impaired QoL [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…However, during long-term follow-up the risk of symptom recurrence is substantial [4], which might adversely influence the outcome and patients' QoL. Although a large number of surveys have explored the QoL during the first few years after CABG [5,6] the experiences of QoL during long time after CABG are limited.…”
Section: Introductionmentioning
confidence: 98%
“…We can estimate an accurate death rate because Western Australia is an isolated state with little emigration of patients in this age group. Bradshaw et al 11 compared the Western Australia death register with the Australian National Death Index in a large cohort of subjects at nearby hospitals undergoing coronary artery surgery during a similar period of time; they found that less than 2% of deaths had been registered outside of Western Australia. If this proportion applied in the current study, then we would estimate that we missed six deaths because they were registered outside of Western Australia.…”
Section: Discussionmentioning
confidence: 99%